2017
DOI: 10.1371/journal.pone.0180006
|View full text |Cite
|
Sign up to set email alerts
|

Negative expectations interfere with the analgesic effect of safety cues on pain perception by priming the cortical representation of pain in the midcingulate cortex

Abstract: It is well known that the efficacy of treatment effects, including those of placebos, is heavily dependent on positive expectations regarding treatment outcomes. For example, positive expectations about pain treatments are essential for pain reduction. Such positive expectations not only depend on the properties of the treatment itself, but also on the context in which the treatment is presented. However, it is not clear how the preceding threat of pain will bias positive expectancy effects. One hypothesis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…This was 267-450ms post-stimulus for the EEP, and 410-645ms for the LEP. Though the LEP latencies are late, similar latencies have been reported in previous studies in response to both CO 2 (Brown, El-Deredy, & Jones, 2014) and thulium laser stimulation (Almarzouki, Brown, Brown, Leung, & Jones, 2017). Each participant’s maximum within this latency was identified, and ±40ms window was extracted around this, to include the peak of the maximum.…”
Section: Methodssupporting
confidence: 87%
“…This was 267-450ms post-stimulus for the EEP, and 410-645ms for the LEP. Though the LEP latencies are late, similar latencies have been reported in previous studies in response to both CO 2 (Brown, El-Deredy, & Jones, 2014) and thulium laser stimulation (Almarzouki, Brown, Brown, Leung, & Jones, 2017). Each participant’s maximum within this latency was identified, and ±40ms window was extracted around this, to include the peak of the maximum.…”
Section: Methodssupporting
confidence: 87%
“…Firstly, is pain catastrophizing characterised by magnified aversive value encoding? Secondly, do pain catastrophizers show evidence of more persistent pain expectancy (the 'prior expectancy effect' (Almarzouki et al, 2017)), which would follow if pain catastrophizing is characterised by perseverative processing of pain cues (I.e., rumination)? In addition to analysing expectancy effects on pain behaviourally, EEG analyses detail the spatiotemporal location and pattern of within-subject effects of cue valuation (visual evoked potential (VEP) responses to cues predicting high vs. low pain) and the effects of prior pain expectancy on the laser-evoked potential (LEP).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we did not find evidence that expectancy effects on nociception and pain were more persistent in the high vs. low PC group after initially negative expectations were updated by contrary information indicating no threat of pain. We previously found that pain perception in healthy individuals undergoing a similar procedure were still influenced by expectations from the initial highly aversive cue, despite the presentation of a second cue to update expectation (the socalled 'prior expectancy effect' (Almarzouki et al, 2017)). However, in this study, although neural activity directly after aversive cues (prior to the second update cues) appeared to be more persistent over the 1.5s analysed in the high vs. low PC group, pointing to greater pain expectancy, none of the analyses (behavioural, univariate EEG or multivariate EEG) provided evidence that prior pain expectancy had a greater influence on pain and nociception in the high PC group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Numerical Rating Scale (NRS) [12], [24], [51], [28], [30], [31], [38], [45], [48]- [50] • NRS variations [14], [22], [27],…”
Section: Pain Perception Testmentioning
confidence: 99%